Perspective: Why Organizational Researchers Should Consider Psychophysiology When Investigating Emotion? - Lajante, Mathieu; Lux, Gulliver (Frontiers in Psychology, 2020)
Although neuroscience is currently gaining wide acceptance in organization science and management studies, some important questions remain unanswered and may hinder the development of so-called organizational neuroscience. Specifically, it appears that the usefulness and the applications of neuroscience methods to organization science are still unclear. Hence, the paper addresses this by examining the role of psychophysiology in investigating implicit emotional experience in organizational behaviors and by discussing how concepts from affective sciences and psychophysiological methods could provide a more complete picture of emotion in organization. Finally, we discuss some important points that should be carefully considered before using psychophysiological measurements in organization science.